High-Efficiency Asymmetric Transmission of Red-Near-Infrared Light Based on Chiral Metamaterial - Tian, Yu; Chen, Zhiwei; Ren, Fang-Fang; Du, Qingguo; Li, Zhengying (Frontiers in Physics, 2021)
It is highly demanded to design and fabricate high-performance polarization converters which exhibit asymmetric transmission for different circularly/linearly polarized light with opposite propagating directions. The asymmetric transmission phenomenon leads to potential applications as isolators and circulators in information and communication systems. We propose a chiral metamaterial structure with high asymmetric transmission efficiency for two linearly orthogonal polarized red-near-infrared light in two opposite incident directions. Theoretical results show that the proposed chiral metamaterial structure achieves cross-polarization conversion where the polarization conversion ratio is over 90% for both forward propagating linearly polarized light and backward propagating orthogonal linearly polarized light from 715 to 810 nm respectively. The physical mechanisms of the polarization converter with asymmetric transmission have been investigated. It is confirmed that the Fabry-Perot like resonance and coupling between electric and magnetic dipoles lead to the highly efficient asymmetric polarization conversion for two orthogonal linearly polarized light. Additionally, the conversion efficiency and bandwidth of polarization converter are successfully optimized by adjusting the related structure parameters.